ALKYLATING AGENT TREATMENT IN CHILDREN WITH STEROID-RESISTANT NEPHROTIC SYNDROME IN WEST JAVA - Widiasta, Ahmedz; Rachmadi, Dedi; Hilmanto, Dany (Indonesian Journal of Health Science, 2025)
Objective: to evaluate SRNS therapy in children. Steroid-resistant nephrotic syndrome (SRNS) is one of the most common causes of chronic kidney disease in children. Kidney Disease Initiative for Global Outcome (KDIGO) no longer recommends an alkylating agent (AA) as the treatment protocol for SRNS, still in some developing countries, such as Indonesia, there are some limitations in obtaining immunosuppressive agents other than AA. Method: Data were collected from the medical records of SRNS children with SRNS aged between 1 and 18 years from January 2016 to December 2021. The data included time to remission, adverse effects, and relapse-free period after receiving AA treatment based on the lesion type. Results: Among the 369 patients enrolled from January 2016 to December 2018, 244 patients (66.12%) had remission with AA, and 125 patients experienced persistent proteinuria. Most of them had remission during the fifth to seventh cycles of intravenous AA (after 6 – 8 months). None of the patients experienced severe adverse effects of AA. Only a small proportion of patients had chronic kidney disease (CKD) stage II–V during follow-up. Conclusions: AA is still effective in treating SRNS in children, with only a few and less harmful adverse effects